Host range of Indian cassava mosaic virus - V. MUNIYAPPA, A.V. MATHEW* and (Indian Phytopathology, 2002)
Indian cassava mo aic virus (ICMV) was transmitted through whitefly, Bemisia tabaci and/or sap to 48 species of plants belonging to Euphorbiaceae and Solanaceae. ICMV was transmitted to Datura stramonium, Manihot esculenta, Manihot glaziovii, Nicandra physalodes, Petunia hybrida and 43 species of Nicotiana. The incubation period varied from 6-40 days depending on the Â species. The ICMV antigen was detected in cassava and other hosts by ELISA.